2010
DOI: 10.1007/s00213-010-1854-3
|View full text |Cite
|
Sign up to set email alerts
|

E-6801, a 5-HT6 receptor agonist, improves recognition memory by combined modulation of cholinergic and glutamatergic neurotransmission in the rat

Abstract: This is the first study to demonstrate that E-6801, a potent 5-HT(6) receptor agonist, improves recognition memory by combined modulation of cholinergic and glutamatergic neurotransmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 80 publications
1
71
2
Order By: Relevance
“…In support of our data in a model of delayinduced deficits, donepezil (0.1-3 mg/kg) alleviates object recognition deficits following a 4 hour inter-trial interval (Kendall et al, 2011). Furthermore, donepezil (0.3 mg/kg) improves object-place-context recognition performance in control rats (Le Cozannet et al, 2010) a task of episodic memory and of particular relevance to impairments observed in Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 82%
“…In support of our data in a model of delayinduced deficits, donepezil (0.1-3 mg/kg) alleviates object recognition deficits following a 4 hour inter-trial interval (Kendall et al, 2011). Furthermore, donepezil (0.3 mg/kg) improves object-place-context recognition performance in control rats (Le Cozannet et al, 2010) a task of episodic memory and of particular relevance to impairments observed in Alzheimer's disease.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, a similar action of an agonist and antagonist of 5-HT6 receptors is not restricted to animal models of depression and anxiety. For instance, both stimulation and blockade of 5-HT6 receptors may exert pro-cognitive actions (Burnham et al 2010;Kendall et al 2011, but see also Meneses et al 2008;Loiseau et al 2008). Similarly, the anti-obesity actions have been demonstrated after administration of both agonists and antagonists of these receptors (reviewed in Heal et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, our present study was designed to examine whether the 5-HT6 receptor agonist EMD 386088 would exert antidepressant-and anxiolytic-like effects in preclinical animal models after intrahippocampal administration. EMD 386088 is a high-affinity (IC50=7.4 nM) full agonist at 5-HT6 receptors (Mattsson et al 2005), and its behavioral effects have been previously demonstrated in animal tasks assessing cognitive functions (Meneses et al 2008;Kendall et al 2011). In the present experiment, the effects of EMD 386088 administration into the CA1 region of the dorsal hippocampus of rats have been investigated in preclinical tests previously used for revealing the antidepressant-and anti-anxiety-like activities of 5-HT6 receptor antagonists after systemic and intrahippocampal ) administrations, i.e., in the forced swim, Vogel conflict, and elevated plus maze tests.…”
Section: Introductionmentioning
confidence: 98%
“…Mitchell and Neumaier 2005). Multiple studies have shown them to improve SOR with delays ranging from 1 min (Woolley et al 2003) to 4 h (King et al 2004;2009;Kendall et al 2011;Schreiber et al 2007) to 24 h or more (Singer et al 2009;Hirst et al 2006;Haydar et al 2010; although see Lieben et al 2005) (Table 4). Some 5-HT6 antagonists induce hypophagia (Bentley et al 1999;Woolley et al 2000), which would confound interpretation of operant tasks motivated by food rewards.…”
Section: Serotoninmentioning
confidence: 93%